O tempo da corpa é o tempo da terra: DanzaMedicina e a (po)ética do gesto que gesta - Cardoso, Morena Santos (2023)
This paper explores how DanzaMedicina – a body psychotherapy practice for women – with its clinical-political-aesthetic potential, can be a rite of subjectivization for the possibility of deviating from the body-system imposed globally and into the skin. Critical thinking, coupled with psycho-emotional care, comes to strengthen the weave between the personal and the transpersonal in the fabric of healing, allowing for the understanding that psychosomatic body patterns are not limited to a biographical context alone. It is about the de-individualization of wounds and the collectivization of and accountability for affections that are not individual because they are generated and contracted through community and collective agreements. To this end, it relies on the invitation to think of danza as a network system of community creation and collective dimension that overflows the own-body and its marks and leaks through the pores to flow together with multiple and polyphonic bodies. It is in order to highlight this nature of dance, that I propose here to replace the “c” by a “z” in its spelling. Breaking the thread that strangles and suffocates life requires that actions in micro and macro-politics spheres engender constant circuits of tension and feedback. To do so, we address first some of the challenges and the limits of the anthropo-phallo-ego-logocentric principle that runs the subjectivity production, under the patriarchal, colonial, and capitalist regime of the unconscious. Tracing this background allows us to point out possibilities of introducing and maintaining a rite of subjectivization which dances with this regime, battling against it, in order to create other choreographies in this sphere, the micropolitical sphere. The chronological history of the female bodies is contextualized along with capitalism different stages of formation and referring to the several strategies of body subjugation that each of those stages articulates in the carving and modulation of the bodies-system throughout five centuries: the violence and the disenchantment (embryonic capitalism), the control and the discipline (industrial capitalism), the exhaustion and the anesthesia (neoliberal financial capitalism). Finally, practical reflections of choreographic disobedience are presented in short reports, which intend to strip the civilizing and pasteurized varnish, twisting, with DanzaMedicina, the movement of the gestures that have been collectively introjected, in order to propose antidotes. The theoretical, inseparably pragmatical, thesis proposed here is that danza, as long as it is linked to an active macro-political perspective beyond the periphery of the skin, contributes to the regeneration, revitalization, and insurrection of female bodies in the face of the fundamental ailments of the present